Kajian keusangan literatur dalam jurnal ilmu komunikasi universitas diponegoro tahun 2021 - Sa’adah, Amanatus; Chusniawati, Tasriatul (Maliki Interdisciplinary Journal, 2025)
The research aimed to analyze the level of obsolescence of literature in scientific articles published in the Journal of Communication Science, Diponegoro University in 2021. There are 16 articles with a total of 446 citations that have a period of publication between 1934 and 2021. The method used in this study is a diachronous obsolescence approach with a half-life calculation technique to determine the median year of reference. The results of the analysis show that the half-life value is in 2014, which means that half of the literature used comes from 2014 to 2021. As a result, citations that are not obsolete reach 52% and the remaining 48% fall into the obsolete category. Which shows that most articles have referred to up-to-date literature, and it is hoped that future authors can improve the quality of the proportion of references as well as encourage the use of more relevant and actual literature in scientific publications.